Progress toward the total synthesis of (+)-Myriceric acid A - Aguilar, Angelo (Kansas State University, 2008)
(+)-Myriceric acid A, [(+)-1.1], is a natural product isolated in 0.01% yield from the southern bayberry, myrica cerifera twigs. It is a specific ETA receptor antagonist because it selectively inhibits the endothelin-1 (ET-1) induced increase in [Ca2+] (IC50 = 11 + 2 nM) and antagonizes the binding of ET-1 (Ki = 66 + 15 nM), in rat aortic smooth muscle cells. ET-1 is a potent vasoconstrictor peptide released by the vascular endothelial cell. Over production of this peptide causes vasospasm, which may lead to heart attack, stroke, pulmonary hypertension, and congestive heart failure. My research involved the development of a total synthesis of (+)-myriceric acid A. This is a triterpenoid compound that has five six-member rings, seven stereo-centers, a carboxylic acid group, and a trans-caffeoyl ester side chain. The synthesis was planned to be accomplished by adding the D and E rings to the known ABC ring compound (4a'S,4b'R,8a'R)-1',1',4a',8a'-tetramethyldecahydro-1'H-spiro[[1,3]dioxolane-2,2'-phenanthren]-8'(3'H)-one [(-)-2.1]. Many model studies, both convergent and linear syntheses, were conducted to determine the best approach to construct the D and E rings. From these studies it was determined that a linear synthesis was best. After the ABCD ring compound (4aR,4bR,6aR,10bR)-1,1,4a,10b-tetramethyl-4,4a,4b,5,6,6a,7,8,10b,11,12,12a-dodecahydro-1H-spiro[chrysene-2,2'-[1,3]dioxolan]-9(3H)-one [(-)-3.41a] was synthesized, several approaches were investigated for the functionalization of the D ring. The best method turned out to be one in which the C14 position of 3.41a was functionalized by a Michael addition of a nitrile group. Conversion of the nitrile to the aldehyde proved to be problematic, but was overcome by the formation of an interesting cyclic hemiiminal which hydrolyzed cleanly to the aldehyde (4aR,4bR,6aR,10aS,10bR,12aR)-1,1,4a,10b-tetramethyl-9-oxohexadecahydro-1H-spiro[chrysene-2,2'-[1,3]dioxolane]-10a-carbaldehyde (4.22) when treated with acid. Herein, the studies that led to the tetra-cyclic aldehyde 4.22, a key intermediate for the synthesis of (+)-myriceric acid A, will be discussed.
Keywords: Myriceric acid A; Synthesis; Chemistry, Organic (0490)